Towards Perpetual Peace: The Dynamics of US and Vietnam Relations Since The Settlement of Agent Orange Case in 2000 - Utama, Bhakti Putra; Pattipeilhy, Shary Charlotte; Windiani, Reni (Global: Jurnal Politik Internasional, 2019)
Agent Orange is a toxic chemical liquid used by the United States military during the Vietnam War in 1955-1975. The use of chemical weapons is classified as a form of crime due to violations of international agreements. This research tries to explain how Agent Orange has become a significant factor in the dynamics of relations between the US and Vietnam. The dynamics will be analyzed using the concept by Immanuel Kant. There are 6 articles that must be done to achieve lasting peace, but this article only discusses articles 1, 5, and 6 which are the basis for the establishment of perpetual peace. Article 1 Perpetual Peace requires a peace agreement that is made as detailed as possible, evidenced by the articles in the 1973 Paris Peace Accord which did not prevent war in the short term, but succeeded in forming a long-term peace scheme. Article 5 Perpetual Peace is also implemented without the intervention of US in Vietnam domestic politics, which until now holds communist ideology. Finally, the US corrective action through the cleaning of the Agent Orange is an embodiment of article 6 of Perpetual Peace. Changes in relations carried out through various collaborations have resulted in a process leading to lasting peace, at least for the US and Vietnam.